Psycholinguistic determinants of reading comprehension in english as a foreign language - Vivaldo-Lima,Javier (2003)
The purpose of this study was to analyze the contribution of linguistic and psychological variables in the explanation of the variance associated with reading comprehension in English (L2). Two hundred and eighty Mexican university students participated in the study. The variables analyzed within the linguistic dimension were: reading strategies in Spanish, linguistic competence in English, and ability to perceive lexical transparency between L1 and L2. The psychological dimension evaluated the influence of the reader’s cognitive style, locus of control, and action control orientation on reading comprehension in L2. Subjects were administered a battery of seven evaluation instruments. Multiple regression analyses suggested a two-stage explanatory model of reading in L2. Firstly, psychological variables accounted for 10.0% of the variance in reading comprehension in the first language. Secondly, reading comprehension in Spanish, linguistic competence in L2, and perception of lexical transparency, accounted for 35.5% of the variance in reading comprehension in English.